Pola Komunikasi Mahasiswa dalam komunikasi virtual pada Aplikasi Whatsapp - Cut Aja Mulia (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Mass media is a communication tool nowadays that has many functions for students' lives in carrying out virtual communication. One of the mass media used for virtual communication by students is WhatsApp. This research uses literature study by comparing and adding references from sources such as books, journals and articles. The aim of this research is to find out how student communication patterns are in virtual communication on the WhatsApp application. The results of this research show student communication patterns using mass media in the form of WhatsApp such as Call Group, Chat Group and Personal Chat. Because WhatsApp can make it easier for students to communicate virtually between fellow students and lecturers.